Medical Record Information System Design of Gadung Health Centers - Sitti Nur Azizah S Ragalutu; Zahra Arwananing Tyas (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Medical Record Information System is a form of puskesmas management information system that can improve the quality of health services. In the medical world, recording patient medical record data is important. The medical record data is used to view the patient's medical history at the time of treatment at health facilities such as puskesmas. The purpose of this study was to design an outpatient medical record information system using the waterfall development method. The results of this research are in the form of business processes and modeling of recommendation systems which are changes from business processes, which are currently running and can be used as a reference for the next stage.